Riparian forest structure and succession in second-growth stands of the central Cascade Mountains, Washington, USA - Villarin, Lauren A.; Chapin, David M.; Jones, John E. (Forest ecology and management, 2009)
We examined the relationship between landform types and riparian forest structure and succession in second-growth stands along mid order streams in the Cascade Mountains, Washington, USA. We sampled tree, sapling, seedling, and shrub characteristics across a range of fluvial geomorphic surfaces, which were classified into four landform classes, including low floodplain, high floodplain, terrace and hillslope. Landform classification was based on topographic characteristics, position relative to the stream channel, and estimated flood frequency. Statistical analyses using generalized estimating equations (GEE) showed that landform exerted a strong influence on the distribution and abundance of conifer and deciduous species and of different tree life stages. The floodplain landforms were characterized by initial disturbance from timber harvest, and ongoing fluvial disturbance, which favored the establishment of deciduous communities dominated by red alder ( Alnus rubra) and maintenance of early successional riparian stands. In contrast, the terrace and hillslope landforms were also subject to timber harvest as the stand initiating agent but were unaffected by fluvial disturbance. However, based on differences in species distribution, we infer that forest structure on these two landforms differed from one another as a result of differences in soil moisture levels. Terraces and hillslopes were found to have high conifer tree abundance, but frequency of younger conifers was higher on hillslopes. Deciduous tree reproduction was very low on terraces and hillslopes. Our results also suggest that conifer recruitment in these second-growth riparian forests may be more successful on soil substrates than on coarse woody debris. We propose that the interplay between the disturbance regime (including type, frequency and intensity) and soil moisture conditions played an important role in influencing the course of riparian succession, present stand structure, and future successional trajectories and these were the primary mechanisms driving vegetation differences among landforms.